Spectral Shift and Split of Harmonic Lines in Propagation Affected High Harmonic Generation in a Long-Interaction Gas Tube - Jozsef Seres; Enikoe Seres; Carles Serrat; Thanh-Hung Dinh; Noboru Hasegawa; Masahiko Ishino; Masaharu Nishikino; Shinichi Namba (Atoms, 2023)
While generating high harmonics in long media of helium gas, at certain laser intensities and chirp, the spectral shift and split of the harmonic lines were experimentally observed, sometimes exceeding one harmonic order. Beyond reporting these results, numerical simulations were performed to understand the phenomenon. A 3D propagation model was solved under the strong field approximation. According to the simulations, the distortion of the laser beam profile during propagation and the consequently accused change in the conditions of phase matching are responsible for the observations. The observed phenomena can be an excellent tool to produce tunable narrow band harmonic sources covering a broad range around 13.5 nm for spectroscopy and for seeding X-ray lasers, and to understand non-desired detuning of the seed wavelength.